The Impact of Paid Family Leave on Families with Health Shocks - Courtney Coile; Maya Rossin-Slater; Amanda Su (Institute of Labor Economics (IZA), 2022)
This paper analyzes the impact of paid family leave (PFL) policies in California, New Jersey, and New York on the labor market and mental health outcomes of individuals whose spouses or children experience health shocks. We use data from the 1996-2019 restricted-use version of the Medical Expenditure Panel Survey (MEPS), which provides state of residence and the precise timing of hospitalizations and surgeries, our health shock measures. We use difference-in-difference and event-study models to compare the differences in post-healthshock labor market and mental health outcomes between spouses and parents before and after PFL implementation relative to analogous differences in states with no change in PFL access. We find that PFL access leads to a 7.0 percentage point decline in the likelihood that the (healthy) wives of individuals with medical conditions or limitations who experience a hospitalization or surgery report "leaving a job to care for home or family" in the post-healthshock rounds. Impacts of PFL access on women's mental health outcomes and on men whose spouses have health shocks are more mixed, and we find no effects on parents of children with health shocks. Lastly, we show that improvements in job continuity are concentrated among caregivers with 12 or fewer years of education, suggesting that government-provided PFL might reduce disparities in leave access.
Keywords: I18; J16; J22; 330; paid family leave; family health shocks; mental health